Human Factors and Usability for Health Information Technology: Old and New Challenges - Carayon, Pascale; Hoonakker, Peter (Yearbook of Medical Informatics, 2019)
Objectives: Despite national mandates, incentives, and other programs, the design of health information technology (IT) remains problematic and usability problems continue to be reported. This paper reviews recent literature on human factors and usability of health IT, with a specific focus on research aimed at applying human factors methods and principles to improve the actual design of health IT, its use, and associated patient and clinician outcomes.Methods: We reviewed recent literature on human factors and usability problems of health IT and research on human-centered design of health IT for clinicians and patients.Results: Studies continue to show usability problems of health IT experienced by multiple groups of health care professionals (e.g., physicians and nurses) as well as patients. Recent research shows that usability is influenced by both designers (e.g., IT vendors) and implementers in health care organizations, and that the application of human-centered design practices needs to be further improved and extended. We welcome emerging research on the design of health IT for teams as team-based care is increasingly implemented throughout health care.Conclusions: Progress in the application of human factors methods and principles to the design of health IT is occurring, with important information provided on their actual impact on care processes and patient outcomes. Future research should examine the work of health IT designers and implementers, which would help to develop strategies for further embedding human factors engineering in IT design processes.
Keywords: Human factors engineering; usability; human-centered design; health information technology; patient safety